Peran Teknologi digital dalam Pembelajaran Serta Pemilihan Metode dan Model untuk Mendukung Pengimplementasian Teknologi digital Dalam Pembelajaran di Sekolah - Mahmudah, Lutfia; Susilawati, Yayuk; Ananya, Nurhayati Oktavia; Anastasia, Devinda (JURNAL DIKDAS, 2025)
Modern education has shifted towards a more dynamic and interactive direction, with the adoption of technology as one of the main strategies in increasing the effectiveness of the teaching and learning process. In this case, learning media is needed that refers to technological developments. To support this, support is needed from selecting appropriate learning methods and models so that learning objectives can be achieved. The method used for the literature review is Systematic Literature Review, using articles that have been collected from Google Scholar and Open Knowledge Maps. The results of this research are to know and understand the role of learning technology in creating an active and participatory learning environment and to know how to choose methods and models. learning that is appropriate to the use of learning media.